Adults with Comorbid Posttraumatic Stress Disorder, Alcohol Use Disorder, and Opioid Use Disorder: The Effectiveness of Modified Prolonged Exposure. Issue 3 (22nd May 2018) - Peck, Kelly R.; Schumacher, Julie A.; Stasiewicz, Paul R.; Coffey, Scott F.
Abstract: Opioid use disorders (OUDs) are a growing problem in the United States. When OUDs co‐occur with problematic drinking and posttraumatic stress disorder (PTSD), negative drug‐related mental and physical health outcomes may be exacerbated. Thus, it is important to establish whether PTSD treatments with established efficacy for dually diagnosed individuals also demonstrate efficacy in individuals who engage in problematic drinking and concurrent opioid misuse. Adults who met DSM‐IV‐TR criteria for PTSD and alcohol dependence were recruited from a substance use treatment facility and were randomly assigned to receive either modified prolonged exposure (mPE) therapy for PTSD or a non‐trauma‐focused comparison treatment. Compared to adults in a non‐OUD comparison group ( n = 74), adults with OUD ( n = 52) were younger, reported more cravings for alcohol, were more likely to use amphetamines and sedatives, were hospitalized more frequently for drug‐ and alcohol‐related problems, and suffered from more severe PTSD symptomatology, depressive symptoms, and anxiety, standardized mean differences = 0.36–1.81. For participants with OUD, mPE was associated with large reductions in PTSD symptomatology, sleep disturbances, and symptoms of anxiety and depression, d s = 1.08–2.56. Moreover, participants with OUD reported decreases in alcohol cravings that were significantly greater than those reported by the non‐OUD comparison group, F (1, 71.42) = 6.37, p = .014. Overall, our findings support the efficacy of mPE for PTSD among individuals who engage in problematic drinking and concurrent opioid misuse, despite severe baseline symptoms.